Entropy-stabilized single-atom Pd catalysts via high-entropy fluorite oxide supports - Haidi Xu (Nature Portfolio, 2020)
Fabricating intrinsically stable single-atom catalysts (SACs) on traditional supports remains a formidable challenge in catalysis. Here, the authors propose a new strategy to construct a sintering-resistant Pd SAC on a novel equimolar high-entropy fluorite oxide.